2014
DOI: 10.2320/matertrans.m2013354
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Structural Rejuvenation in Zr<sub>50</sub>Cu<sub>40</sub>Al<sub>10</sub> Metallic Glass Strained by Torsional Straining at Elevated Temperature

Abstract: Zr 50 Cu 40 Al 10 metallic glass was deformed by high pressure torsion at different temperatures. Thermal analysis reveals that the structural relaxation peak is intensified not only by increasing rotation revolutions, but also raising deformation temperature. The relaxation enthalpy in the sample deformed at 373 K for 10 revolutions shows similar value to the one deformed at room temperature for 50 revolutions, suggesting the analogous structural rejuvenation. Extensive atomic movement leads to the pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This estimate is consistent with previous experimental evaluations of alloys with the same composition, with T g = 706 K (433°C) and T x = 792 K (519°C). [24][25][26] Hence, crystallization processes might affect the hardness values measured at 500°C.…”
Section: Resultsmentioning
confidence: 99%
“…This estimate is consistent with previous experimental evaluations of alloys with the same composition, with T g = 706 K (433°C) and T x = 792 K (519°C). [24][25][26] Hence, crystallization processes might affect the hardness values measured at 500°C.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] Among them, rejuvenation, a process in which more free volume is involved and the energy state is increased, has attracted much attention. [21][22][23] A series of rejuvenation methods by capitalizing various mechanical or thermal treatments have been developed for rejuvenating the glassy materials, for example, plastic deformation, 24,25 thermal cycling, 21 shot peening, 26 and ion irradiation. 27 These methods provide the possibility to solve the aging problem in the applications of MGs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, structural rejuvenation has attracted much attention from researchers owing to its great importance in the metallic glass elds. For instance, it has been reported that a change in ductility by the rejuvenation is exhibited compared with the as-cast and relaxed states [1][2][3][4][5] . This result clearly indicates that the mechanical properties can be controlled by the rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discussions regarding the glassy state and the crystallization process of the rejuvenated metallic glass are still not suf cient. Most of the rejuvenation methods (e.g., high pressure torsion 2,3) , shot peening 7) , irradiation 8) and so forth) are based on a mechanical or physical damage inducing process (e.g., severe plastic strain, irradiation and so forth) to acquire a high rejuvenation amount. In short, a destruction of the initial glassy structure or a signi cant deformation (i.e., large change of shape) are always inevitable when these methods are applied.…”
Section: Introductionmentioning
confidence: 99%